Upaya Meningkatkan Asertivitas Melalui Layanan Bimbingan Kelompok - Sukiah Sukiah (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This research was carried out based on the phenomenon that occurred in SMP Negeri 12 Pekanbaru which showed low student assertiveness. This is indicated by the tendency of students who are silent during the process of teaching and learning activities, and students do not dare to ask about subject matter that has not been understood. The purpose of this study is to find out group guidance services can increase the assertiveness of class IX.1 students of SMP Negeri 12 Pekanbaru. The population in this study were students of class IX.1 of SMP Negeri 12 Pekanbaru. The sampling technique used in this study is random sampling, by taking a random sample of students totaling 20 students. Based on the results of a comparison analysis of the total results of pre-test and post-test in the experimental group and the control group obtained differences between the experimental group and the control group. In the experimental group the mean pre test was 66% and in the post test it was 83%. In the control group the mean pre test was 65% and in the post test it was 66%. It was concluded that the condition of student assertiveness after the implementation of group guidance services in the experimental group on average the students experienced an increase in percentage so that it was included in the high category (83%). While the condition of student assertiveness in the control group who were not given group guidance service activities, the average student also experienced an increase in the percentage included in the medium category (66%). Keywords: assertiveness, group guidance Abstrak: Penelitian ini dilaksanakan berdasarkan fenomena yang terjadi di SMP Negeri 12 Pekanbaru yang menunjukkan rendahnya asertivitas siswa. Hal tersebut ditunjukkan dengan kecenderungan siswa yang diam pada saat proses kegiatan belajar mengajar, serta siswa tidak berani bertanya tentang materi pelajaran yang belum dipahami. Tujuan penelitian ini untuk mengetahui layanan bimbingan kelompok dapat meningkatkan asertivitas siswa kelas IX.1 SMP Negeri 12 Pekanbaru. Populasi dalam penelitian ini adalah siswa kelas IX.1 SMP Negeri 12 Pekanbaru. Teknik sampling yang digunakan dalam penelitian ini adalah random sampling, dengan mengambil sampel siswa secara acak yang berjumlah 20 siswa. Berdasarkan hasil analisis perbandingan hasil total pre test dan post test pada kelompok eksperimen dan kelompok kontrol didapat perbedaan antara kelompok eksperimen dan kelompok kontrol. Pada kelompok eksperimen mean pre test 66% dan pada post test menjadi 83%. Pada kelompok kontrol mean pre test 65% dan pada post test menjadi 66%. Disimpulkan bahwa kondisi asertivitas siswa setelah pelaksanaan layanan bimbingan kelompok pada kelompok eksperimen rata-rata siswa mengalami peningkatan persentase sehingga termasuk dalam kategori tinggi (83%). Sedangkan kondisi asertivitas siswa pada kelompok kontrol yang tidak diberikan kegiatan layanan bimbingan kelompok, rata-rata siswa juga mengalami peningkatan persentase yang termasuk dalam kategori sedang (66%). Kata kunci: asertivitas, bimbingan kelompok